PENENTUAN LOKASI PRIORITAS PENANGANAN KASUS DEMAM BERDARAH DI KOTA SEMARANG BERBASIS SISTEM INFORMASI GEOGRAFIS (Faculty of Social Science, Universitas Negeri Semarang, 2013)
Moving from concern about the high rate of morbidity due to dengue hemorrhagic fever (DHF) in the city, which reached 2,685 people until late July of 2009, this research is done. The basic method used in this research is the approach that is deskriptif.This method research is found that the spatial distribution pattern of dengue cases in the city, tend to cluster. Factors that influence the environment: temperature, precipitation, humidity, river distance, topography, population density, residential density and power flying mosquito Aedes aegypti. Almost all in sub-urban locations in the city of Semarang included in the first priority because it exceeds the handling of dengue morbidity nasional.Therefore recommended further research with larger scale arena and detail, whether at the district or sub-district level.